Визначення воску і воскоподібних сполук методом високотемпературної хроматографії - Кіщенко, В. А. (НТУ "ХПІ", 2014)
В статье изложены результаты исследований содержания восков и воскоподобных веществ в подсолнечном масле методом газожидкостной хроматографии с использованием высокотемпературной колонки. Изложено методику выделения восков с методом колоночной хроматографии с использованием набивных колонок с силикагелем.

In the article the results of studies of wax and wax-like compounds content in sun-flower seed oil be mean gas-liquid chromatography with using high-temperature column are presented. The method of extraction of waxes with using of column’s chromatography on the silicagel stuffed columns.
Determinftion of waxes and wax-like compounds by mean high-temperature chromatography
Keywords: харчові жири; олії; тверді воски; рослинні воски; соняшникова олія